PENGARUH INOKULASI FUNGI MIKORIZA ARBUSKULA (FMA) DAN PUPUK P TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN AKAR WANGI (vetiveria zizanoides L.) - Intan Suwanti; Ratih Kurniasih; Putri Irene Kanny (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2023)
Vetiver (Vetiveria zizanioides L.) is a plant that produces essential oils. The use of mycorrhiza and P fertilizer on vetiver plants can support growth and increase root crop production. However, the exact dose of P fertilizer is not yet known to increase and support the growth and production of vetiver plants. For this reason, the dose of fertilization treatment was carried out to see which doses could be associated with Arbuscular Mycorrhizal Fungi (AMF) which could help the growth of vetiver plants. This study used a factorial Randomized Block Design (RAK) with two factors. The first factor was AMF inoculation consisting of 2 levels, without AMF inoculum (M0) and inoculum administration (M1). The second factor is the dose of Phosphor (P) fertilizer consisting of 3 levels, namely, the dose of 50% P fertilizer as much as 397 mg/polybag (P1), 100% P fertilizer at 793 mg/polybag (P2) and 150% P fertilizer as much as 1,190 mg/polybag (P3 ). The results showed that the AMF inoculum had not been able to increase the growth and yield of vetiver plants. AMF inoculum affects the number of spores and root infections. P fertilizer has not been able to increase the growth and production of vetiver plants. There was no interaction between the two treatments.